2006
DOI: 10.1016/j.virol.2006.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of the unclassified bovine enteric virus Newbury agent-1 (Newbury1) endorses a new genus in the family Caliciviridae

Abstract: The pathogenic bovine enteric virus, Newbury agent-1 (Bo//Newbury1/1976/UK), first identified in 1976, was characterized as a possible calicivirus by morphology, buoyant density in CsCl and the presence of a single capsid protein but genomic sequence could not be obtained. In the present study, the complete genome sequence of Newbury1 was determined and classified Newbury1 in a new genus of the Caliciviridae. The Newbury1 genome, of 7454 nucleotides, had two predicted open reading frames (ORFs). ORF1 encoded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
79
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 50 publications
6
79
1
2
Order By: Relevance
“…4-8.3 kb (Kapikian et al, 1996). This family has four accepted genera, Lagovirus, Norovirus, Sapovirus and Vesivirus (Green et al, 2000), and two putative novel genera, Becovirus (Oliver et al, 2006) and Recovirus (Farkas et al, 2008), which have recently been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4-8.3 kb (Kapikian et al, 1996). This family has four accepted genera, Lagovirus, Norovirus, Sapovirus and Vesivirus (Green et al, 2000), and two putative novel genera, Becovirus (Oliver et al, 2006) and Recovirus (Farkas et al, 2008), which have recently been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…4-8.3 kb (Kapikian et al, 1996). This family has four accepted genera, Lagovirus, Norovirus, Sapovirus and Vesivirus (Green et al, 2000), and two putative novel genera, Becovirus (Oliver et al, 2006) and Recovirus (Farkas et al, 2008), which have recently been proposed.Studies on the replication of most caliciviruses have been hampered severely by the lack of a reliable cell-culture system. More recently, cell-culture systems have been developed for some caliciviruses such as porcine enteric calicivirus (Parwani et al, 1991), murine norovirus 1 (Wobus et al, 2004) and human noroviruses (Straub et al, 2007).…”
mentioning
confidence: 99%
“…The family includes the Vesivirus, Lagovirus, Norovirus, and Sapovirus genera as well as unassigned viruses [2]. The member viruses of each genus share a common genomic organization and a high degree of sequence similarity [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Also, antibodies to marine and terrestrial vesiviruses and vesivirus genome sequences have been detected in blood donors in the United States [13]. Animal enteric caliciviruses genetically related to human NoVs and SaVs have been detected in pigs and cows [2,[14][15][16][17][18][19][20][21]. Antibodies to human NoV have been detected in pigs and antibodies to bovine NoV have been detected in humans [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Sapoviruses (SaVs), members of the genus Sapovirus, are small, non-enveloped, positive sense, single-stranded RNA viruses that belong to the family Caliciviridae (Oliver et al, 2006). Porcine SaV was first identified in a faecal sample of a diarrhoeic piglet (Sus scrofa f. domestica) by electron microscopy in the United States in 1980 (Saif et al, 1980;Guo et al, 1999) and later the pathogenic potential of porcine SaV was demonstrated in experimental infections of gnotobiotic pigs (Flynn et al, 1988;Guo et al, 2001).…”
mentioning
confidence: 99%